2014
DOI: 10.1002/ejoc.201402886
|View full text |Cite
|
Sign up to set email alerts
|

A Scalable Synthesis of the Antidepressant Agomelatine by a Tandem Allylic Chlorination–Isomerization Process

Abstract: A concise, scalable, and industrially applicable process for the synthesis of the antidepressant agomelatine is described. The process relies on a tandem allylic chlorination–isomerization sequence, on a tetralone‐derived allyl carbinol, as the key transformation. The target compound is obtained in five steps from commercially available 7‐methoxy‐1‐tetralone, in 52.3 % overall yield after final recrystallization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Aer a simple re-crystallization, the pure molecule 317 was obtained with a purity of more than 99.5% (Scheme 48). 217,218…”
Section: Iridium-catalysed Reactionsmentioning
confidence: 99%
“…Aer a simple re-crystallization, the pure molecule 317 was obtained with a purity of more than 99.5% (Scheme 48). 217,218…”
Section: Iridium-catalysed Reactionsmentioning
confidence: 99%
“…7-methoxy-1-tetralone (MT) is mainly used as the organic material or intermediate in chemical engineering currently (12)(13)(14)(15). Our research group revealed that wild Juglansshurica leather has strong anti-tumor effects through the long-term study, while MT may be one of the effective components.…”
Section: Introductionmentioning
confidence: 99%